2009
DOI: 10.1007/s11886-009-0020-1
|View full text |Cite
|
Sign up to set email alerts
|

Heart-brain interactions in mental stress-induced myocardial ischemia

Abstract: Myocardial ischemia, which results from emotional provocation, occurs in as many as 30–50% of patients with CAD during the discourse of their daily lives. This emotionally provoked or mental stress ischemia is associated with the poor prognosis, with emerging treatment strategies. This chapter will outline the conceptual constructs which support the pathophysiologic underpinnings, and biobehavioral aspects associated with this mental stress ischemia. We will review a biobehavioral model where cognitive stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 61 publications
2
31
0
Order By: Relevance
“…Similarly, other studies have found that psychosocial characteristics of post-MI subjects, especially anxiety and depressive symptoms, are associated with higher levels of reported angina [32, 33]. It is also possible that a confluence of factors is necessary to trigger angina during everyday life, including subjective emotional distress and physiological changes in the neuroendocrine and vascular milieu, potentially leading to coronary microvascular dysfunction [34, 35]. Thus, psychosocial mechanisms underlying the propensity to develop ischemia with mental stress in the laboratory could be important contributing factors for angina symptoms in everyday life.…”
Section: Discussionmentioning
confidence: 91%
“…Similarly, other studies have found that psychosocial characteristics of post-MI subjects, especially anxiety and depressive symptoms, are associated with higher levels of reported angina [32, 33]. It is also possible that a confluence of factors is necessary to trigger angina during everyday life, including subjective emotional distress and physiological changes in the neuroendocrine and vascular milieu, potentially leading to coronary microvascular dysfunction [34, 35]. Thus, psychosocial mechanisms underlying the propensity to develop ischemia with mental stress in the laboratory could be important contributing factors for angina symptoms in everyday life.…”
Section: Discussionmentioning
confidence: 91%
“…It has also been reported that the anorexic effect of BDNF might correlate with the levels of several cerebral peptides such as leptin or cholecystokinin, which also have peripheral effects on cardiovascular diseases. [ 33 53 54 ] Second, all subjects with obesity underwent both diet restriction and exercise promotion. We previously reported that an increase in muscle power after aerobic exercise promotion, independent of body-weight change, could increase fasting serum BDNF [37] .…”
Section: Discussionmentioning
confidence: 99%
“…20 These vasomotor effects likely occur through the activation of stress-response systems; indeed, plasma catecholamines increase rapidly with mental stress and correlate with hemodynamic changes. 21 Mental stress can also induce cardiac electrical instability, as shown by an increase in T-wave alternans and other measures of abnormal cardiac repolarization that are predictors of cardiac arrhythmias and sudden cardiac death. 2224 …”
Section: Discussionmentioning
confidence: 99%